Global migration futures: exploring the future of international migration with a scenario methodology - Vezzoli, S; Bonfiglio, A; de Haas, H (International Migration Institute, 2017)
Preparing for future changes in international migration requires an understanding of the different ways in which societies may change and how these will affect migration patterns. This requires us to move beyond traditional approaches of migration forecasting, which tend to focus on a limited set of relatively certain, easy-to-predict factors, such as demographic trends, and which assume structural continuity, by exploring methodologies that are suited to examine factors such as geopolitical shifts, economic restructuring, technological change and environmental change, which are notoriously difficult to predict, but which we cannot afford to ignore, since they will have a considerable impact on global migration patterns and trends. To this end, this paper presents the Global Migration Futures (GMF) Scenario Methodology developed at the University of Oxford’s International Migration Institute (IMI). The GMF Scenario Methodology integrates insights from migration theory with techniques from the Intuitive Logics School of scenario planning to enable the simultaneous and systematic examination of relatively certain and uncertain migration determinants, their future evolution as well as their implications for population mobility. In addition, this paper discusses the key insights gained through the application of the GMF Scenario Methodology in different world regions as well as its main limitations.